Traces of Old Visual Patterns in the Romanian Modern Painting - BARBU, Virginia; TEACĂ, Corina (Studia Universitatis Babeș-Bolyai Dramatica, 2019)
The contribution intents to stretch out the way certain visual sequences of old Romanian or Byzantine art are brought back to life in the Romanian modern age. Some study cases reveal specific ways of using and understanding the cultural tradition. In the first two decades of the 20ᵗʰ century the artistic research regarding the past is connected to the concept of national identity. One of the pioneers in this field was the theorist artist Apcar Baltazar, well-known for his attempts to construct a “national style” on the basis of Romanian folk elements and the post-Byzantine style. His viewpoint on a modern national style established upon past decorative patterns, indebted to Symbolism and the international style Art Nouveau, represents a start in developing spiritualized forms inspired from archaic arts. The discourse on history, in the manner of eclectic quotations from the painting of Baltazar, was exceeded by history itself. The First World War changed life and art, increasing the dramatism of image, the harsh simplicity of line, the flattening of color present in the entire production of the generation of artists grouped in 1920 around the association Arta Română (Romanian Art). Artists like Tonitza, Dimitrescu, Sion, Șirato reinterpreted and adapted the aesthetics of Romanian old mural painting and rustic elements to the modern artistic language. The Byzantine tradition, a long-lasting paradigm (in the situation in which artists accepted commands of the Christian Orthodox Church as a way of living), was lightly assimilated by strong personalities, but tangible in the propaganda discourse of the Neo-Orthodox movement.